Analisis Peranan Manajemen Sumber Daya Manusia Pada Umkm Telekomunikasi Disa Cloud - Daffa, Muhammad Ammar; Fadili, Dadan Ahmad (Syntax Literate, 2025)
This study analyzes how human resource management (HRM) influences business performance and sustainability in a micro, small, and medium enterprise (MSME) operating in the telecommunications sector, namely Disa Cloud, located in Bekasi. The research is motivated by the critical role of effective human resource management in enhancing competitiveness and long-term viability of MSMEs amid rapid technological change in the telecommunications industry. A qualitative research approach was employed using a combination of literature study, in-depth interviews, and direct observation. Primary data were collected through interviews with the owner and employees of Disa Cloud, complemented by on-site observations to gain a comprehensive understanding of HR practices, organizational culture, and operational dynamics. The findings indicate that well-implemented HRM practices—such as clear job division, employee training and skill development, effective communication, and performance evaluation—have a positive impact on employee productivity, service quality, and overall business performance. Moreover, good HR management contributes to employee motivation, adaptability to technological changes, and organizational resilience, which are essential for sustaining growth in the telecommunications sector. However, challenges remain in terms of limited resources and the need for more structured HR planning. This study provides practical insights for MSME owners, particularly in the telecommunications industry, on the importance of strengthening HR management as a strategic asset. The results can serve as a reference for developing more effective and sustainable HRM strategies in similar MSMEs.